"Aku Senyum, Aku Dapet Pahala": Living Hadits tentang Anjuran Senyum pada Anak-anak di Banyumas, Indonesia - Khayati, Nimatul; Patty, Muh Akbar; Rahmi, Lailatul (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2024)
This study examines the implementation of the living hadith on smiling, as recommended by the Prophet Muhammad, among early childhood education at RA Masyithoh 20 Sibalung, an Islamic kindergarten in Banyumas, Central Java Province of Indonesia. Smiling, as outlined in the hadith, is considered a form of charity that fosters social interaction, empathy, and emotional development. The research employs an ethnographic approach, involving direct observations, interviews with teachers, and discussions with pupils, to understand how the hadith is integrated into daily practices. The study reveals that the practice of smiling, both as an individual and social behavior, contributes to a positive school environment, enhances social bonds among pupils, and serves as a foundation for both spiritual and emotional growth. Teachers at RA Masyithoh 20 Sibalung model this behavior, explaining the underlying values of the hadith to the pupils, and encouraging them to smile not only as a social gesture but as a form to expect reward from Allah. Despite its benefits, the research identifies several challenges, such as the lack of consistency in smiling practices at home and school, children’s emotional instability, and the need for enhanced parent-teacher collaboration. This study highlights the importance of integrating Islamic teachings into early childhood education, particularly through the practice of smiling, which not only aligns with religious values but also promotes the development of prosocial behaviors in young children.